Pilot study of Corridor use by African elephants (Loxodonta africana) in Ol Pejeta Conservancy, Laikipia District, Kenya - Sernert, Henriette (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
The African elephant (Loxodonta africana) has lost more than 50 % of its range to human civilisation. The remaining lands still used by the elephants are fragmented into smaller blocks with or without connection between them (IUCN, 2011; IEF, 2014; IUCN Red List, 2015). The loss of available lands and the settlement of humans in previous elephant areas has resulted in conflict between the species. Elephants can destroy water supplies, ruin houses, raid and ruin crops and grain stores. They are also known to kill livestock and injuring or killing people. Elephants are hunted and killed both because these conflicts and because of their tusks that is sold as ivory on the black market (IUCN, 2011; IEF, 2014; IUCN Red List, 2015). In order to protect the elephant population and minimise the conflicts with humans knowledge of elephant requirements and movements are crucial (IUCN, 2011; IEF, 2014; IUCN Red List, 2015). In Africa there are many protected areas of varying sizes. Several of these protected areas are fences and some have wildlife corridors in their fences allowing different species to freely enter or exit the area. The aim of this study is to examine the elephant’s usage and what influences the usage of the wildlife corridors in Ol Pejeta Conservancy in the Laikipia District, Kenya. Furthermore to evaluate the planned methods of data collection with camera traps at the corridors. The elephants used the corridors frequently and their preferred time of traveling through the corridors were during the dark hours of the day when 60% of the passages were made. Single elephants used the corridors with a higher frequency than Family Groups and Adult Groups. A correlation of the corridor use and moon phase was found but no correlation with precip. The camera traps where used for collection of data on all animals using the corridors and therefore the cameras was set too low to give a clear view when elephants passed too close to the camera.